High Performance Cu-Ti Alloy Wires Prepared By Over-Aging and Intense Cold-Drawing - Satoshi Semboshi; Yusuke Kadoi; Naoya Masahashi; Yasuyuki Kaneno; Takayuki Takasugi (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
Cu–Ti alloy wires doped with and without a small amount of Ni were fabricated by over-aging and using intense drawing procedures. For both the Cu–Ti alloys with and without Ni doping, the over- aged microstructure was occupied fully with a coarse lamella of Cu solid solution and β-Cu4Ti plates precipitated discontinuously by grain boundary reactions. The full-lamellar microstructure was developed much more rapidly by aging in multi steps at 873 K to 723 K rather than by isothermal aging at 723 K. Ni doping in Cu-Ti alloy was also effective to accelerate the formation of the lamellar microstructure. When drawing the over-aged alloy with inferior hardness but superior electrical conductivity, the strength increased steadily and eventually exceeded that for the wires drawn from the peak-aged alloy. In addition, the electrical conductivity of the wires drawn from the over-aged alloy was always much greater than that from the peak-aged alloy. Eventually, the procedure of over-aging, followed by intense drawing, could enhance both the strength and electrical conductivity of Cu-Ti alloys, whichever they contain a small amount of Ni or not, rather than the conventional peak-aging and drawing process. INTRODUCTION Cu-based alloy wires, which have an excellent combination of strength and electrical conductivity, have attracted extensive attention for highly mechanically stressed electrical devices, such as conductive lead wires and wires in suspension springs. Cu-Be alloys are widely used for such electrical components owing to their combination of strength and electrical conductivity among industrial Cu-based alloys. However, since beryllium is potentially toxic and also a rare element, substitute materials for Cu-Be alloys have been searched for several decades. Age-hardenable Cu–Ti based alloys have been proposed as candidates because their mechanical and physical properties are comparable to those of Cu-Be alloys; however, their electrical conductivity is inferior (Datta & Soffa, 1976; Soﬀa & Laughlin, 2004). In order to satisfy the requirement of downsizing and streamlining electrical devices, further improvement of the mechanical and electrical properties of Cu–Ti alloy wires is needed. Age-hardenable Cu–Ti alloys, which contain approximately 3 to 6 at.% Ti, are typically prepared using a solid solution treatment above 1100 K and then aging at a moderate temperature of 700 K to 800 K. It has been revealed that the microstructural events during aging progress as follows (Soﬀa & Laughlin, 2004): (1) compositional modulation of the parent supersaturated Cu solid solution in an initial aging stage (Laughlin & Cahn, 1975), (2) continuous nucleation and growth of fine needle-shaped precipitates of metastable β’-Cu4Ti with a tetragonal structure in a peak-aged stage, and (3) discontinuous precipitation of cellular components laminating the plates of a terminal Cu solid solution and stable β-Cu4Ti with an orthorhombic structure at the grain boundaries in an over-aging stage. It has been also accepted that the highest number density of dispersed fine β’-Cu4Ti needles should contribute to maximal strengthening. On the other hand, decease of the strength in the over-aging stage occurs due to the replacement of the fine β’- Cu4Ti needles with cellular components containing coarse β-Cu4Ti plates, while the electrical conductivity is significantly enhanced due to the depletion of solute Ti in the Cu matrix. This suggests that a combination of strength and electrical conductivity for age-hardenable Cu-Ti alloys is in a trade-off relationship, and that innovative improvement of both properties might be limited to tuning the aging conditions.